Analisis Metode Penerjemahan Novia Stephani dalam Menerjemahkan Novel Ms. Wiz Loves Dracula Karya Terence Blacker: Array - Arsitawaty, Sindy; Ilmi, Djauzi (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2022)
The research deals with an analysis of translation method in the translated novel by Terence Blacker titled Ms Wiz Loves Dracula translated into Ms Wiz Jatuh Cinta pada Dracula by Novia Stephani. The objectives of the research were (1) to find out the types of translation method in the novel, (2) to find out the most dominant translation methods the novel. The researcher was conducted by using descriptive quantitative research. The data were words, phrases and sentences on Ms Wiz Loves Dracula as source of the data. The data were analyzed by using translation method focused on SL emphasize based on Newmark (1988) and process of translation method also based on Newmark (1988:19). The result of this research were (1) the types of translation method were 32 word for word (55%) and 26 literal translation (45%), (2) the dominant types of translation method was word for word (55%).